G103(P) Children's epilepsy surgery service in England: Audit of activity and outcome. (27th April 2016) - Agrawal, SK; Philip, S; Varadkar, S; Martland, T; Carter, M; Harkness, W; Cross, JH; Verity, C; Walsh, R
Abstract : Objective: To examine trends in epilepsy-related surgical procedures (ERSPs), excluding vagal nerve stimulator procedures, in children performed at the four CESS centres in England since inception of the service in November 2012. To analyse outcome and follow-up data at one year, identify potential treatment gaps in different geographical areas, raise awareness about surgery as an option for medically refractory epilepsies, and reflect on challenges encountered since the inception of the CESS. Methods: Epilepsy-related surgical activity for the first 20 months of CESS service (Nov 2012–June 2014- first period) was compared with a more recent 18 months (April 2014–Sep 2015- second period). Data was collected from the four CESS centres with regard to referrals, case evaluation, surgical procedures and outcome. The number of referrals to CESS for the commissioning year 2014–15 was compared to the expected number based on an epidemiological cohort. 1 Adverse surgical outcomes were measured using the GOSH adverse surgical grading score. Results: There were 183 ERSPs in the first period compared to 271 in the second period representing time-adjusted increase in activity of 61%. In 2014–15 commissioning year, 387 children were referred to the 4 CESS centres for consideration of epilepsy surgery (excludes VNS referrals), representing between 30–50% of expected numbers based on the previous epidemiological cohort. 1 There is considerable variation in referral rates from different areas in England. Twelve months following surgery, 95 (58%) of children were Engel Class I (seizure-free) with 141 (87%) Engel Class I-III. Best outcomes were achieved with temporal lobe surgery with 77% seizure-free at 1 year. There were no mortalities but there were two unexpected surgery-related morbidities in this group. Conclusion: There has been a major change in the children's epilepsy surgery landscape in England since the inception of CESS, with a significant year-by-year increase in ERSPs during the study period. Outcomes by Engel classification remain equivalent to published international outcomes. The mortality rate has been zero with low surgical morbidity. Reference: Berg et al . Frequency, prognosis and surgical treatment of structural abnormalities with MRI in childhood epilepsy. Brain 2009;132 :2785–97